RELEASE OF ANTHOCYANINS FROM CHITOSAN FILMS CROSS-LINKED WITH SODIUM TRIPOLYPHOSPHATE - Carlos-Salazar, Max J. (2017)
Chitosan and depolymerized chitosan films cross-linked with sodium tripolyphosphate were prepared and loaded with anthocyanin extracted from purple corn. The effect of sodium tripolyphosphate concentration, cross-linking time, thickness and molar mass of chitosan on the delivery of anthocyanin were studied. The results showed a lower percentage of available anthocyanin (from 29 % to 10 %) in the films more cross-linked, it staying the remaining anthocyanin in the film. This percentage was influenced by the other factors mentioned above. The release kinetics has been studied to elucidate the drug release mechanism. All films was controlled by Fick’s law when fitted to the Higuchi model. For the determination of the diffusion exponent, the results were fitted to the Korsmeyer-Peppas model. The films showed different mechanisms of release, including a Fickian and a non-Fickian diffusion process.